Exploring CSR and Financial Performance in Oil and Gas Industry - Tanaya, Olivia (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2022)
Paris Agreement requires many firms, regions, and nations to put more attention on corporate social responsibility (CSR). However, not all industries could move into climate change mitigation easily. Oil and gas industry is one of industries that have dilemma. This industry is highly contributed to gas emission, but they cover it by becoming the leading of CSR activities. On the other hand, doing CSR requires firms for using their resource for non-profitable purposes. This condition gets worse due to in recent years oil and gas industry struggles to operate their business. Hence, the decision for doing CSR needs to be evaluated. This research aims to determine the impact of corporate social responsibility (CSR) on the firm’s financial performance which uses a fixed effect of panel data model for the study period from 2015-2019. Based on the results, CSR, especially social dimensions can increase the firm’s financial performance in the short term. It enables firms to build a good reputation which can attract more investors who consider the social impact of their investment portfolio. Further, since the impact of CSR is more pronounced in the economic downturn, it may not be effective in the future market value.